PENGARUH PENGGUNAAN MODUL PEMBELAJARAN LANGSUNG DAN MINAT MENULIS TERHADAP KEMAMPUAN MENULIS DESKRIPSI SISWA KELAS X SMA MUHAMMADIYAH PRINGSEWU TAHUN PELAJARAN 2015/2016 - Anggraeni, Leni; Puspita, Dian; Astuti, Sariyah (JURNAL MANAJEMEN PENDIDIKAN ISLAM AL-IDARAH, 2016)
The purpose of that is expected from this research is to find out the average difference between the students' ability to write descriptions of learning that using direct learning model with conventional ones, to know the effect of the interaction effect of the use of direct instructional model and the interest in writing to the ability to write descriptions that siswa.Penelitian conducted an experimental study. Data analysis or testing the hypothesis using Analysis of Variance (Anova) two paths followed by t test Dunnet.Penelitian experiments have been carried out concluded that on average the ability to write descriptions of students who use the direct learning model is higher than the average writing skills descriptions of students using model konvensional.Selain it is known that there is an interaction effect using a model of learning and interest in writing to the ability to write a description. Learning that using direct learning model to the students who have a high interest in writing, the average ability to write descriptions are higher than using conventional learning. There were no significant differences in average ability to write a description of your using direct and conventional learning in students who have a low interest in writing. Thus the direct learning model has a positive influence on learning, especially writing a description.